1998
DOI: 10.1093/ejo/20.5.501
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of bass, bionator and twin block appliances. Part I - the hard tissues

Abstract: A prospective clinical study with a random allocation of 47 adolescent patients to three different functional appliance groups was established and compared with an untreated control group over a 9-month period. Treatment was undertaken with either a Bionator, Twin Block, or Bass appliance. Pre- and post-treatment cephalograms were used to quantify the skeletal and dentoalveolar changes produced by the appliances and compared with those observed in the control group as a result of growth. Both the Bionator and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
104
2
27

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 48 publications
29
104
2
27
Order By: Relevance
“…As for the dentoalveolar changes, a contribution to overjet correction in the bionator group was provided by both proclination of the lower incisors and retroclination of the upper incisors in the short term, thus confirming the findings of Illing et al 8 However, most of these differential changes in dental inclination diminished at the long-term observation. The comparison on the overall observation period showed only a slight residual palatal inclination of the upper incisors in the treated group (about 1.5 degrees more than in untreated controls).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As for the dentoalveolar changes, a contribution to overjet correction in the bionator group was provided by both proclination of the lower incisors and retroclination of the upper incisors in the short term, thus confirming the findings of Illing et al 8 However, most of these differential changes in dental inclination diminished at the long-term observation. The comparison on the overall observation period showed only a slight residual palatal inclination of the upper incisors in the treated group (about 1.5 degrees more than in untreated controls).…”
Section: Discussionsupporting
confidence: 84%
“…The overbite was reduced by about 3 mm in the bionator group when compared with the controls long-term. A previous prospective clinical trial 8 with short-term observations reported similar findings for changes in the vertical dentofacial components induced by the bionator.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Second, most comparable studies [7][8][9][10][11][12] may have only included Class II division 1 malocclusions (not always clear from the selection criteria), whereas a proportion (18%) of the current sample could likely have been classified as Class II division 2. Therefore, the comparisons that follow must be interpreted with prudence.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,19,28 The proclination of mandibular incisors was probably due to mesial force on mandibular incisors induced by protrusion of mandible. 16,29 Toth and McNamara 16 concluded that lingual tipping of the maxillary incisors is due to the contact of the lip musculature during Twin-block treatment. This lingual tipping can also be due to the labial wire in Bionator and twin block appliances, which might come into contact with the incisors during sleeping, causing them to retract.…”
Section: Dental Effects Of Twin Blocksmentioning
confidence: 99%